MANAJEMEN PENGADUAN MASYARAKAT DALAM PEMBERIAN SANTUNAN KECELAKAAN LALU LINTAS DI KANTOR PT. JASA RAHARJA KOTA MAKASSAR - Andi Jaya Samudra; Lukman Hakim; Ruskin Azikin (Department of Public Administration, Muhammadiyah University of Makassar, 2019)
The objective of this research is to know the management of public complaints in the provision of traffic accidents compensation in PT. Jasa Raharja office of Makassar City. The type of this research is descriptive qualitative research with phenomenological type . The data are collected by interviews, observation and documentation. The result of this research reveals that the management of public complaints in the provision of traffic accidents compensation in PT. Jasa Raharja office of Makassar City is not optimal, because there is still demerit toward compensation provision, such as the clarity of public complaints management, certainty of time is not maximal yet, and there is still complaint of the public about the distribution which makes public waiting for long time and unsatisfied. That is a proof that the management needs improvement.